Historical Review: Problematic Malaria Prophylaxis with Quinine - Shanks, G. Dennis (Am J Trop Med Hyg, 2016)
Quinine, a bitter-tasting, short-acting alkaloid drug extracted from cinchona bark, was the first drug used widely for malaria chemoprophylaxis from the 19th century. Compliance was difficult to enforce even in organized groups such as the military, and its prophylaxis potential was often questioned. Severe adverse events such as blackwater fever occurred rarely, but its relationship to quinine remains uncertain. Quinine prophylaxis was often counterproductive from a public health viewpoint as it left large numbers of persons with suppressed infections producing gametocytes infective for mosquitoes. Quinine was supplied by the first global pharmaceutical cartel which discouraged competition resulting in a near monopoly of cinchona plantations on the island of Java which were closed to Allied use when the Japanese Imperial Army captured Indonesia in 1942. The problems with quinine as a chemoprophylactic drug illustrate the difficulties with medications used for prevention and the acute need for improved compounds.